2016
DOI: 10.1080/07420528.2016.1194289
|View full text |Cite
|
Sign up to set email alerts
|

Wearing blue light-blocking glasses in the evening advances circadian rhythms in the patients with delayed sleep phase disorder: An open-label trial

Abstract: It has been recently discovered that blue wavelengths form the portion of the visible electromagnetic spectrum that most potently regulates circadian rhythm. We investigated the effect of blue light-blocking glasses in subjects with delayed sleep phase disorder (DSPD). This open-label trial was conducted over 4 consecutive weeks. The DSPD patients were instructed to wear blue light-blocking amber glasses from 21:00 p.m. to bedtime, every evening for 2 weeks. To ascertain the outcome of this intervention, we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…In line with our results, Esaki et al. () found that DLMO and sleep onset advanced in patients with delayed sleep phase syndrome after 2 weeks of wearing blue‐light‐blocking glasses in the evening (Esaki et al., ). Another study found a similar advance by using blue‐light‐blocking glasses in conjunction with supplementary light in the morning, but also enforced earlier bedtimes (in contrast to our protocol that allowed subjects to freely choose when they retired to bed; Appleman et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, Esaki et al. () found that DLMO and sleep onset advanced in patients with delayed sleep phase syndrome after 2 weeks of wearing blue‐light‐blocking glasses in the evening (Esaki et al., ). Another study found a similar advance by using blue‐light‐blocking glasses in conjunction with supplementary light in the morning, but also enforced earlier bedtimes (in contrast to our protocol that allowed subjects to freely choose when they retired to bed; Appleman et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…The change in measured activity could be due to a shift in the diurnal variation previously demonstrated in the PIPR . In a similar study in which subjects with delayed sleep phase disorder wore blue light‐blocking glasses from 9:00 pm to bedtime, dim light melatonin onset was shown to advance by 78 min . While the previous study did not measure pupil responses, circadian shifts in melatonin suggest that the ipRGCs may also be undergoing circadian changes, as the ipRGC pathway ultimately leads to the pineal gland to control the release of melatonin.…”
Section: Discussionmentioning
confidence: 81%
“…36 In a similar study in which subjects with delayed sleep phase disorder wore blue light-blocking glasses from 9:00 pm to bedtime, dim light melatonin onset was shown to advance by 78 min. 53 While the previous study did not measure pupil responses, circadian shifts in melatonin suggest that the ipRGCs may also be undergoing circadian changes, as the ipRGC pathway ultimately leads to the pineal gland to control the release of melatonin. The increase in PIPR seen here suggests that a clinically significant change was induced in the ipRGCs as seen by the subsequent downstream increase in night-time melatonin and increase in objectively measured sleep duration.…”
Section: Discussionmentioning
confidence: 95%
“…No severe side effects were reported, but two manic patients had emerging depressive symptoms that were diminished in less than 1 day [25]. Other trials have also used blue-blocking glasses at night as a treatment for sleep-wake disorders and affective disorders [26][27][28][29]. Still, these trials have been small and/or in homogeneous samples with a specified disorder, and have required the study participants to adhere to a protocol at specified times of the day (resting in forced darkness or wearing glasses).…”
Section: Introductionmentioning
confidence: 99%